2019
DOI: 10.1177/1747493019879662
|View full text |Cite
|
Sign up to set email alerts
|

Emotions after stroke: A narrative update

Abstract: Aim In this narrative review we aimed to describe how stroke affects emotions and update the readers on the emotional disturbances that occur after stroke. Methods We searched Medline from 1.1.2013 to 1.7.2019, personal files and references of selected publications. All retrieved systematic reviews and randomized controlled trials were included. Other references were selected by relevance. Summary of review The emotional response includes a reactive behavior with arousal, somatic, motivational and motor compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 96 publications
0
17
0
Order By: Relevance
“…Even early neuropsychiatric disorders after stroke (NDS) may increase the risk of mortality and recurrence in patients with stroke[ 4 , 5 ]. The current management and treatment of the majority of NDS is not satisfactory, except for some antidepressants that show therapeutic benefit[ 3 , 6 ]. Patients with NDS do not even benefit from existing advanced medical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Even early neuropsychiatric disorders after stroke (NDS) may increase the risk of mortality and recurrence in patients with stroke[ 4 , 5 ]. The current management and treatment of the majority of NDS is not satisfactory, except for some antidepressants that show therapeutic benefit[ 3 , 6 ]. Patients with NDS do not even benefit from existing advanced medical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that a substantial number of stroke survivors develop long term mental health problems such as anxiety, anger, depression, fear and others that have a negative influence on recovery, limit social reintegration of the persons with stroke, reduce quality of life, and are a source of caregiver burnout [ 6 ]. Moreover, previous research has associated delirium with an increased risk of long term mental health problems in different in-hospital populations; however, the data are equivocal [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Agitation and aggression: Agitation, inability to control anger and aggression are observed symptoms in PWA[ 22 , 36 , 131 ]. Anger represents an emotional reaction, whereas aggressiveness is understood as the subsequent behavioral reaction[ 132 ].…”
Section: Resultsmentioning
confidence: 99%
“…In general, NPS are a frequent and challenging consequence of stroke, derived from the crossroad of lesion-related brain factors and psychological distress related to the event and its functional impact in daily life[ 16 , 17 ]. Several comprehensive reviews dealing with NPS in post-stroke patients have been reported[ 18 - 22 ] and a recent original study evaluating 518 non-aphasic stroke patients found that half of the sample presented at least one NPS based on Neuropsychiatric Inventory (NPI)[ 23 , 24 ]. However, one relevant limitation of the above studies is that they exclude aphasic participants due to the inherent linguistic-assessment difficulties[ 25 - 29 ].…”
Section: Introductionmentioning
confidence: 99%